Simply home decorating : stylish and beautiful ideas for every room = Simply home organizing : peaceful and orderly ideas for every room - Michaels, Melissa, 1967- (Ten Peaks Press, an imprint of Harvest House Publishers, 2023)
Home decorator extraordinaire Melissa Michaels, creator of the award-winning blog The Inspired Room, shares over 600 of her best organizing and decorating tips to help you bring more order and beauty to your home. Start creating your sanctuary today.